A companion to the anthropology of the Middle East - Altorki, Soraya (Hoboken, NJ : Wiley-Blackwell, 2015)
"A Companion to the Anthropology of the Middle East presents a comprehensive overview of current trends and future directions in anthropological research and activism in the modern Middle East"--
Notes on Contributors -- Acknowledgments -- Preface -- Part I. Introduction: Theoretical and Conceptual Issues -- Enduring Concerns, Resilient Tropes, and New Departures: Reading the Companion / Deniz Kandiyoti -- Theory and Thematics in the Anthropology of the Middle East / Suad Joseph -- Structure/Agency and the Anthropology of the Middle East / Soraya Altorki -- Reflections on the Politics of Middle East Studies / Steven C. Caton -- Part II. Culture and Everyday Life -- The Politics of Aesthetics in the Muslim Middle East / Martin Stokes -- Dreams and the Miraculous / Amira Mittermaier -- Refiguring Islam / Nada Moumtaz -- In the Garden of the Sexes: Of Men, Women, Gaze, and Hair / Shahla Haeri -- Trajectories of Gendered Labor / Livia Wick -- The Politics of Poetry / J. Andrew Bush -- Part III. Social Relations and Social Movements -- Medical Anthropology in the Middle East and North Africa / Jessica Newman and Marcia C. Inhorn -- From Rural Development to Environmental Anthropology / Nicholas S. Hopkins -- Displacement and Dispossession in the Middle East / Dawn Chatty -- Anthropology and Humanitarianism in the Middle East / Ilana Feldman -- Anthropologies of Middle Eastern Diasporas / Paul A. Silverstein -- The Invention of the Mizrahim / Ella Shohat -- The Mizrahi Cinema of Displacement / Ella Shohat -- Social Movements and Revolution / Zeina Zaatari -- Part IV. Law, Politics, and the State -- Justice between Islamic Sharia and Liberal Law: Remarks on the Egyptian Context / Hussein Ali Agrama -- The Notion of Arab Culture and the "Colonial Present" / Mayssoun Sukarieh -- Rethinking Anthropology of Neoliberalism in the Middle East / Julia Elyachar -- "States of Aspiration": Anthropology and New Questions for the Middle East / Michelle Obeid -- Rethinking the "Post-Ottoman": Anatolian Armenians as an Ethnographic Perspective / Hakem Al-Rustom -- Reframing the Middle Eastern City: Thoughts on New Research / Kamran Asdar Ali -- Part V. Pop Culture and New Media -- Middle Eastern Music and Popular Culture / John Philip Rode Schaefer -- New Media and Electronic Networks / Mark Allen Peterson -- Index.
Includes index.
Includes bibliographical references and index at the end of each chapters.
Print version record and CIP data provided by publisher.
Keywords: Ethnology -- Middle East; SOCIAL SCIENCE / Anthropology / Cultural; Social Science; Ethnology; Manners and customs; Middle East -- Social life and customs; Middle East; Electronic book; Electronic books; Electronic books